1992
DOI: 10.1093/oxfordjournals.aje.a116365
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Aging on Plasma Sex Hormones in Men: The Telecom Study

Abstract: From April 1985 to July 1987, 1,408 healthy white men aged 20-60 years in Paris, France, recruited on an occupational basis, underwent a physical examination and measurements of plasma sex hormones in a cross-sectional study. Both total testosterone and estradiol showed a significant stepwise decrease with age (p less than 0.001) starting in the early adult years, while estrone did not vary. These relations of testosterone and estradiol with age remained significant after adjustment for body mass index, subsca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
2
7

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(86 citation statements)
references
References 0 publications
2
75
2
7
Order By: Relevance
“…They concluded that diabetes, instead of the medication itself, is the reason for the diabetes-cancer association. The finding of a negative association between prostate cancer and diabetes duration supports the hypothesis of a hormonal mechanism in the protection for prostate cancer in diabetic patients [34,49].…”
Section: Treatment Of Type 2 Diabetes and Cancersupporting
confidence: 72%
“…They concluded that diabetes, instead of the medication itself, is the reason for the diabetes-cancer association. The finding of a negative association between prostate cancer and diabetes duration supports the hypothesis of a hormonal mechanism in the protection for prostate cancer in diabetic patients [34,49].…”
Section: Treatment Of Type 2 Diabetes and Cancersupporting
confidence: 72%
“…Increased age is one of the strongest predictors for coronary artery disease. The Telecom Study demonstrated a significant decrease in testosterone concentration with each decade of life [26]. Both mean intima-media thickness and plaque score, determined by carotid ultrasonography, have been proven to be inversely associated with serum free testosterone concentration in our previous study [27].…”
Section: Discussionmentioning
confidence: 55%
“…A large number of studies demonstrated general decline in serum levels of testosterone among men over 50 years of age [Gray et al 1991;Simon et al 1992;Belanger et al 1994;Ferrini and Barrett-Connor 1998]. Previous reports from animal studies indicate that the epididymis undergoes morphological changes with aging, that probably affects sperm maturation.…”
Section: Discussionmentioning
confidence: 99%